Enhancement of Protein S Anticoagulant Function by β2-glycoprotein I, a Major Target Antigen of Antiphospholipid Antibodies: - Merrill, Joan T.; Wei Zhang, Hong; Shen, Christine; Butman, Bryan T.; Jeffries, Eddie P.; Lahita, Robert G.; Myones, Barry L. (Thrombosis and Haemostasis, 1999)
Thrombosis in the antiphospholipid syndrome has been associated with acquired deficiency of the anticoagulant protein S. We sought evidence that β2-glycoprotein I, a major target antigen for antiphospholipid antibodies, is involved in regulation of protein S activity. Incubation of purified protein S or plasma with β2-glycoprotein I reversed functional modulation of protein S by its plasma inhibitor, the C4b-binding protein. In a plasma-free ELISA, β2-glycoprotein I prevented the binding of protein S and C4b-binding protein when pre-incubated with immobilized protein S but not when similarly preincu-bated with C4b-binding protein. β2-glycoprotein I in fluid phase interfered with precipitation of protein S by sepharose-bound C4b-binding protein. Effects of β2-glycoprotein I on protein S function were inhibited by one of four monoclonal anti-β2-glycoprotein I antibodies. These data suggest that β2-glycoprotein I helps maintain adequate plasma levels of circulating free, active protein S. Antiphospholipid (anti-β2-glycoprotein I) antibodies might cause sporadic thrombosis, at least in part, by impairing this novel regulatory mechanism.